The role of identity in digital consumer behavior: A conceptual model and research propositions based on gender - Natalia Rogova; Shashi Matta (AMS Review, 2022)
Nowadays consumers can express their identities not only through their possessions and buying behavior, but also using social media and digital networks. This article aims to understand these digital consumer behaviors by focusing on identity strength and the identity signaling phenomenon. We develop a conceptual model that combines internal and external factors to explain the intensity and content of digital identity-related behaviors. We use the example of gender identity to build our research propositions, as gender is one of the most frequently and intensely debated identities in online consumer discussions. Further, we propose how digital and offline identity signaling behaviors are intertwined, and discuss the online behaviors of trans consumers. In doing so, our conceptual work highlights the unique features of digital identity signaling behaviors as well as the complexity of identities, including gender, and provides useful insights for researchers and marketers.
Keywords: 330; Digital consumer behavior; Identity; Gender identity; Identity signaling; Gender role beliefs